Design and AC Loss Analyze of a 10 MW-Rated HTS Wind Turbine Generator - Inanir, F.; Erciyas, A.; Terzioglu, R. (SPRINGER, 2022)
We present key design parameters of an innovative 10 MW low-speed direct-drive superconducting generator by high-temperature superconductor coated conductors for the rotor windings. In the simulations, the generator has an iron rotor with the superconducting coils operating at 20 K while the rotor core and the cooper stator are at room temperature. The calculations have been performed by Finite Element Software Comsol Multiphysics. Electromagnetic design parameters, magnetic flux distributions, phase current, voltage, and loss distributions of the superconducting generator are introduced. In addition, the AC losses that arise during the current increase in the superconducting rotor were calculated separately using both the H- and AV-formulation forms of Maxwell's equations employing the non-linear current-voltage relation of the superconductor. The current distribution and magnetic field distribution of the superconductor coils, volumetric loss density distribution, and comparison of the losses of each coil layer have been analyzed and discussed in detail.
Keywords: High-temperature superconductor; REBCO coated conductor; Wind turbine generator; H- and A-V formulation; Finite element method; HTS rotating machines; Physics